Hubungan Paritas Dengan Kejadian Anemia Pada Ibu Hamil di PMB Pratama Madina Medan Tembung Kabupaten Deli Serdang Tahun 2024 - Basaria Manurung; Emma Dosriamaya Noni Br Simanjuntak (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Anemia is a condition of hemoglobin (Hb) levels in the blood (Hb <11gr/dl) caused by a lack of nutrients needed for the formation of hemoglobin. This condition causes new problems for babies, such as low birth weight, decreased immune status, possible physiological disorders, and infant growth and development. This study aims to determine the Relationship between Parity and the Incidence of Anemia in Pregnant Women at PMB Pratama Madina Medan Tembung, Deli Serdang Regency in 2024. This type of research is an analytical survey study with a cross-sectional method approach. The population is all pregnant women at PMB Pratama Madina Medan Tembung as many as 30 people. The number of samples used was 30 people obtained using the Total sampling technique. The data analysis technique used chi square. the results obtained in this study were from 30 respondents, there was a relationship between Parity and the Incidence of Anemia in Pregnant Women showing that the p value = 0.015 <0.05. It is recommended for Health Workers to increase counseling related to the Incidence of Anemia in Pregnant Women.